2013
DOI: 10.1371/journal.pone.0081339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lycium Barbarum (Wolfberry) Polysaccharides on Preserving Retinal Function after Partial Optic Nerve Transection

Abstract: Lycium Barbarum Polysaccharides (LBP) are the active components of Wolfberry (a traditional Chinese medicine) which has long been used for improving visual function. This study aims to investigate localized changes of retinal function in a partial optic nerve transection (PONT) model, and effects of LBP on visual function. The multifocal electroretinograms (mfERG) were obtained from 30 eyes of 30 Sprague-Dawley rats. The rats were divided into 6 groups (five treatment groups and one control group). Starting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
(80 reference statements)
0
38
0
3
Order By: Relevance
“…In addition to the primary and secondary degeneration of RGCs, the mfERG study showed that outer retinas (photoreceptors and bipolar cells) could also be affected subsequently after PONT, and L. barbarum could reverse the functional deterioration caused by primary and secondary degeneration of the outer and inner retina (Chu et al 2013). This protective effect might be related with the antioxidant effect of LBP and the inhibition of the JNK pathway ).…”
Section: The Effects Of L Barbarum On Secondary Degeneration Of Rgcsmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition to the primary and secondary degeneration of RGCs, the mfERG study showed that outer retinas (photoreceptors and bipolar cells) could also be affected subsequently after PONT, and L. barbarum could reverse the functional deterioration caused by primary and secondary degeneration of the outer and inner retina (Chu et al 2013). This protective effect might be related with the antioxidant effect of LBP and the inhibition of the JNK pathway ).…”
Section: The Effects Of L Barbarum On Secondary Degeneration Of Rgcsmentioning
confidence: 97%
“…Although it seems that some RGCs will take a longer time period to die than others after CONT, the occurrence of secondary degeneration after CONT is uncertain because all the axons are transected, and the degeneration of axons can lead to the degeneration of RGC bodies. This model has been used extensively for studying the mechanisms of secondary degeneration and the possible neuroprotective agents from its establishment (Yoles and Schwartz 1998;Levkovitch-Verbin et al 2003;Fitzgerald et al 2009aFitzgerald et al , b, 2010aLevkovitch-Verbin et al 2010;Selt et al 2010;Levkovitch-Verbin et al 2011;Payne et al 2011Payne et al , 2012Wells et al 2012;Chu et al 2013;Cummins et al 2013;Fitzgerald et al 2013;Li et al 2013;Payne et al 2013;Savigni et al 2013;Szymanski et al 2013). However, the number of axons influenced was unknown and the intact and damaged axons were mingled together.…”
Section: Secondary Degeneration After On Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Goji is a good source of fiber, protein, carotenoids [3], and polysaccharides [4]. Recent research indicates that goji had a lot of biological activities, including antidiabetes [5], antiproliferative activity [4], preserving retinal function [6], and antioxidant activity [7,8]. A lot of research has focused on carotenoids [3] and polysaccharides [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research indicates that goji had a lot of biological activities, including antidiabetes [5], antiproliferative activity [4], preserving retinal function [6], and antioxidant activity [7,8]. A lot of research has focused on carotenoids [3] and polysaccharides [4,6]. However, phytochemicals [9,10], such as phenolic compounds [11], including phenolic acids and flavonoids in goji and their antioxidant activity have been less evaluated.…”
Section: Introductionmentioning
confidence: 99%